2011
DOI: 10.1088/0953-8984/23/29/295701
|View full text |Cite
|
Sign up to set email alerts
|

Theory of high-TCsuperconductivity: transition temperature

Abstract: The superconducting transition temperatures of high-T C compounds based on copper, iron, ruthenium and certain organic molecules are discovered to be dependent on bond lengths, ionic valences, and Coulomb coupling between electronic bands in adjacent, spatially separated layers. 1 Optimal transition temperature, denoted as T C0 , is given by the universal expression k B T C0 = e 2  / ℓζ; ℓ is the spacing between interacting charges within the layers, ζ is the distance between interacting layers and  is a uni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
157
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(170 citation statements)
references
References 138 publications
12
157
0
Order By: Relevance
“…Superconductivity in these systems breaks down as intralayer Coulomb repulsion and charge scattering become increasingly important with decreasing ℓ. Equation (1) has been validated and β confirmed through extensive study of experimental results for high-T C compounds based on cuprate [7,9], ruthenate, rutheno-cuprate [7], iron-pnictide [7], iron-chalcogenide [8], organic [7], and intercalated group-5-metal nitride-chloride [27,28] structures, with T C0 ranging from 6.3 K to 145 K.…”
Section: Relation Of Fractional Charge σ To T C0mentioning
confidence: 71%
See 3 more Smart Citations
“…Superconductivity in these systems breaks down as intralayer Coulomb repulsion and charge scattering become increasingly important with decreasing ℓ. Equation (1) has been validated and β confirmed through extensive study of experimental results for high-T C compounds based on cuprate [7,9], ruthenate, rutheno-cuprate [7], iron-pnictide [7], iron-chalcogenide [8], organic [7], and intercalated group-5-metal nitride-chloride [27,28] structures, with T C0 ranging from 6.3 K to 145 K.…”
Section: Relation Of Fractional Charge σ To T C0mentioning
confidence: 71%
“…By adopting this model that takes the two types of charge reservoirs into account, it has been shown that the optimal transition temperature T C0 , corresponding to the highest T C for a given compound structure, is given by the algebraic equation [7], where ζ is the interaction distance (measured along the transverse or hard axis), A is the basal-plane area per formula unit, σ/A is the areal charge density per type I layer per formula unit for participating charges and β (= 0.1075 ± 0.0003 eV Å 2 ) is a universal constant, and where e -2 β is approximately twice the reduced electron Compton wavelength. Superconductivity in these systems breaks down as intralayer Coulomb repulsion and charge scattering become increasingly important with decreasing ℓ.…”
Section: Relation Of Fractional Charge σ To T C0mentioning
confidence: 99%
See 2 more Smart Citations
“…12 In applied fields other studies have shown sub-gap peaks at ~5.5 meV for tunnelling into the vortex core region [71,72]; these were interpreted as evidence of bound quasiparticles in a discrete energy state that theoretically is allowed only for a nodeless gap, noting that d-wave pairing symmetry would yield a continuum in quasiparticle states [23]. Coexisting hole and electron carriers found in Hall effect studies [73] have recently been identified with the two spatially separated electronic bands involved in high-T C pairing; manifestations of superconductivity is considered to have dependence on relative band sensitivities in experiment as discussed in [74].…”
Section: Dominant Superconducting Gap Symmetrymentioning
confidence: 99%